Neuropsychological heterogeneity in executive functioning in autism spectrum disorders. (July 2014) - Geurts, Hilde; Sinzig, Judith; Booth, Rhonda; HappÉ, Francesca
<x content-type="archive" xml:space="preserve">Abstract</x> In most research it is common to report results on a group level. For example, various studies report that children and adults with autism show executive function deficits. However, studies often differ in the pattern of findings. We believe this might be partly due to the heterogeneity of the autism population. Put differently, some people with autism might indeed have executive dysfunctions, but this does not mean that everybody with autism has such a deficit. In the current study we re-analysed published data from children with autism, children with Attention Deficit/Hyperactivity Disorder (also associated with executive dysfunction) and children without a clinical diagnosis. A surprisingly small number of children did indeed have executive function deficits. However, children with a clinical diagnosis had executive function deficits more often than those without a diagnosis. These findings show us that besides reporting findings on a group level, researchers need to report findings on an individual level. Understanding the differences between individuals with autism might help us in pinpointing differences in etiology, prognosis, and treatment response. Different subsets of autism symptoms might be genetically partly independent. With respect to cognition, this may imply that one cognitive theory is unlikely to explain all symptoms and that there will be large individual differences in cognitive deficits/assets between individuals with autism. However, most journal articles report only group differences, treating individual differences more or less as 'noise' in the data. In the current study, we reanalyzed data from three independent studies (totaling 93 children with autism spectrum disorders (ASDs), 104 children with attention deficit hyperactivity disorder (ADHD), and 93 typically developing children) to examine the degree of heterogeneity in executive function deficits. The three main findings were that (1) only a small percentage of children with ASD had a significant deficit in measured executive function; (2) there is not just heterogeneity within ASD groups, but also across studies, and (3) in line with Nigg and colleagues (2005), only a small number of children with ADHD showed a significant inhibitory control deficit. Executive (dys)function cannot be a marker for ASD as defined in the DSM, but might have potential as a specifier like IQ and language. This is in line with the idea that the executive function account cannot be a sole explanation for ASD. The findings do suggest that an individual differences approach might give us more information on potential subtypes within the autism spectrum. Future research is needed to define and test neuropsychological subtypes and their external correlates, including etiology, prognosis, and treatment response.